Knowledge, attitudes and practices towards HPV infections, complications of HPV infections and the HPV vaccine among students of Medical Science in North Macedonia - Ana Marja Radevska; Edmond Brava; Keti Skeparovska; Ivana Gacova; Alexandra Micevska; Vanya Rangelova; Dejan Jakimovski; Elena Valkanova (Royal Academy of Medicine of the Balearic Islands, 2024)
Introduction: Human papillomavirus (HPV) is one of the most common causes of sexually transmitted diseases. The HPV vaccine is crucial in the primary prevention of HPV infection and associated diseases and complications. This objective of the study was to determine the knowledge, attitude and practices of the Medical students in North Macedonia towards HPV infections, complications of HPV infections and the HPV vaccine. Materials and methods: In the period of November 2022 – December 2022 a study using a semi - structured questionnaire was conducted in Medical Faculties in North Macedonia, covering 728 people over 18 years old that are medical students. Standard descriptive statistics were used to summarize the demographic characteristics. Results: A total of 728 participants took part in the survey, predominantly female (n=601, 82.5%). Around one third of all respondents (36.4%) have received the HPV vaccine. We established a statistically significant difference between the vaccinated and non-vaccinated respondents in terms of gender (χ2=22.231, p<0.001) and this proved to be the strongest predictor for vaccination in the logistic regression analysis. The main driver for hesitation regarding the HPV vaccine was the fear of possible side effects and there was an association between the fear of possible side effects and the probability for vaccination (15.1%% (n=40) vaccinated vs. 41.2% (n=191) non-vaccinated students, χ2=73.020, p<0.001). The students who didn’t agree with the statement that recommending the HPV vaccine to teenagers will send a message that it is okay to become sexually active at an early age were 1.89 times more likely to have been vaccinated. Conclusions: The current study demonstrated that medical students in North Macedonia had a suboptimal uptake of the HPV vaccine. To increase the coverage, it is essential that people get the right information. Having doubts about the vaccine’s safety and effectiveness is the main cause of vaccination hesitancy.
Keywords: HPV; vaccine; Knowledge; attitudes; practices